Akanie as a Means of Linguistic Stylization in Lithuanian Novels by Józef Weyssenhoff - Płusa, Magdalena (Respectus Philologicus, 2018)
[only abstract in English; full article and abstract in Polish]Józef Weyssenhoff (1860–1932) was a Polish writer who dedicated to Kaunas, Lithuania two of the most significant novels in his literary output – “Unia” (1910) and “Soból i panna” (1912), often called “Lithuanian novels”. He was deeply emotionally connected with this region since he was a child. Both these texts constitute a valuable source of knowledge concerning the status of regional variant of Polish language and its formal characteristics that were used in the ground-breaking decades of the 19th and 20th century. These characteristics were used by the writer as a means of masterly conducted linguistic stylization. Among the presented by Weyssenhoff’s linguistic facts characteristic for Northern Borderlands there can be found a process called ‘akanie’ what basically means the pattern of pronouncing unstressed vowels /e/ and /o/ as /a/. Which of the peculiar indicators concerning the specific vowel pronunciation is evidenced in the studied texts (phonetic parameter or a phenomenon that has experienced morphological processes)? How do they serve as a means of linguistic stylization? The following article presents a brief description of the peculiar process called ‘akanie’ which was known to Józef Weyssenhoff from Kaunas, Lithuania and which he then deliberately introduced in his two novels as a function of a literary manifestation.
Keywords: ‘Akanie’, Polish Language of Northern Borderland, “Soból i panna”, “Unia”, Weyssenhoff